TI_GERICHTE 52.2018.126 vom 30. Januar 2018 , Licenza edilizia per la costruzione di posteggi fuori zona edificabile - TI Tribunale d'appello (2018)
Licenza edilizia per la costruzione di posteggi fuori zona edificabile